Role of OsFKBP62-OsHSP90-OsHSFA2 pathway in regulating thermotolerance in rice (Oryza sativa L.) - Ng'ang'a, Maureen (2025)
Heat stress is a major factor limiting crop productivity with global warming increasing the frequency and intensity of high temperature events. Rice (Oryza sativa L.) is staple food crop for over half of the world’s population. However, the growth, yield and grain quality of rice are adversely affected by heat stress. Analyses into the molecular mechanisms, physiological features and genes underlying high temperature tolerance are fundamental in developing heat-resilient rice varieties in the face of climate change. The study dissected the molecular basis of the OsFKBP62-OsHSP90-OsHSFA2 pathway in response to elevated temperature through subcellular localisation assessment and gene expression profile analyses. It was observed that the genes were localized in different cellular compartments with high temperature influencing the cellular localisation of OsHSP90.1. At high temperature cytoplasmic localized genes, OsFKBP62a and OsFKBP62c were co-expressed with OsHSP90.1 in the nucleus. The study demonstrated the presence of a bipartite nuclear localization sequence (NLS) in OsFKBP62b and OsHSP90.1 and two monopartite NLS in OsHSFA2a. Interestingly, gene expression analysis in rice spikelets during anthesis revealed that OsFKBP62b, OsHSP90.1 and OsHSFA2a were found to be strongly induced under high temperature and identified as potential gene targets for improving reproductive heat tolerance. Overexpression of OsHSFA2a resulted in rice plants with enhanced photosynthetic heat tolerance. Conversely, OshsfA2a knock-out mutants were heat sensitive and exhibited a rapid decline in chlorophyll fluorescence and lower spikelet fertility compared to wild-type plants under high temperature. This data indicated that OsHSFA2a improved thermotolerance in rice vegetative and reproductive tissue. In conclusion, the results provided insights into the molecular mechanism of the OsFKBP62-OsHSP90-OsHSFA2 pathway and potential targets that could be useful in improving thermal resilience in rice cultivars.